Adsorption of Ammonia in Wastewater Using Hyacinth (Eichornia Crassipes) Powder with The Assistance of Bio Balls - M. Ilham Nurdin; Arifah Sukasri; Jeanne Dewi Damayanti (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Water pollution can be caused by the discharge of domestic wastewater containing contaminants. Ammonia is a water pollutant that has a bad impact because it can cause an unpleasant pungent odor and can inhibit or stop the growth of aquatic organisms because it interferes with oxygen binding, changes pH and affects enzymatic reactions and membrane stability in aquatic organisms. This research treats domestic wastewater contaminated with ammonia by means of adsorption using water hyacinth powder. In order to reduce ammonia contaminants in domestic wastewater. This study used a quantitative method which included the acclimatization stage, preliminary test, water hyacinth powder production, adsorption process, ammonia content analysis. The results showed that the use of water hyacinth powder in the most efficient adsorption process was 8 grams of water hyacinth powder and 60 bioballs in 10 liters of wastewater with a decrease in ammonia content of 93.47% for 24 hours. With the bioremediation process ratio, the ammonia content in wastewater can be reduced from 4.810 ppm to 0.314 ppm.Keywords:Adsorption, Domestic Wastewater, Ammonia, Water Hyacinth Powder